Evidence for Stress-like Alterations in the HPA-Axis in Women Taking Oral Contraceptives. Issue 1 (December 2017) - Hertel, Johannes; König, Johanna; Homuth, Georg; Auwera, Sandra; Wittfeld, Katharina; Pietzner, Maik; Kacprowski, Tim; Pfeiffer, Liliane; Kretschmer, Anja; Waldenberger, Melanie; Kastenmüller, Gabi; Artati, Anna; et al.
Abstract Using oral contraceptives has been implicated in the aetiology of stress-related disorders like depression. Here, we followed the hypothesis that oral contraceptives deregulate the HPA-axis by elevating circulating cortisol levels. We report for a sample of 233 pre-menopausal women increased circulating cortisol levels in those using oral contraceptives. For women taking oral contraceptives, we observed alterations in circulating phospholipid levels and elevated triglycerides and found evidence for increased glucocorticoid signalling as the transcript levels of the glucocorticoid-regulated genesDDIT4 andFKBP5 were increased in whole blood. The effects were statistically mediated by cortisol. The associations of oral contraceptives with higherFKBP5 mRNA and altered phospholipid levels were modified by rs1360780, a genetic variance implicated in psychiatric diseases. Accordingly, the methylation pattern ofFKBP5 intron 7 was altered in women taking oral contraceptives depending on the rs1360780 genotype. Moreover, oral contraceptives modified the association of circulating cortisol with depressive symptoms, potentially explaining conflicting results in the literature. Finally, women taking oral contraceptives displayed smaller hippocampal volumes than non-using women. In conclusion,  the integrative analyses of different types of physiological data provided converging evidence indicating that oral contraceptives may cause effects analogous to chronic psychological stressors regarding the regulation of the HPA axis.